Kinetics and mechanism of the chromium(vi) catalyzed decomposition of hypochlorous acid at elevated temperature and high ionic strength. Issue 11 (16th February 2018) - Kalmár, József; Szabó, Mária; Simic, Nina; Fábián, István
Abstract : The decomposition of hypochlorous acid was studied under industrially relevant conditions (6.0 M NaClO3, 80 °C). Chromium(vi ) catalyzes the decomposition and the catalytically active form is CrO4 2− . A detailed kinetic model is proposed for the process. Abstract : An important reaction step in the industrial production of NaClO3 (electrochemical chlorate process) is the thermal decomposition of HOCl/OCl − to yield ClO3 − and Cl − . It is widely accepted that this reaction is accelerated by aqueous chromium(vi ) species. A detailed kinetic study was conducted under industrially relevant conditions, i.e. at high ionic strength (6.0 M) and elevated temperature (80 °C), to investigate this phenomenon. The decomposition of hypochlorous acid was followed in the presence of Cr(vi ) or phosphate (PO4 3− ) or without any additive. In addition to the beneficial pH buffering effect of Cr(vi ), the CrO4 2− form of chromium(vi ) was found to slightly catalyze the decomposition of hypochlorous acid. The overall rate of HOCl decomposition can be expressed as −d c HOCl /d t = k dec [HOCl] 2 [OCl − ] + k cat [HOCl] 2 [CrO4 2− ]. The corresponding rate constants were determined, k dec = 9.4 ± 0.1 M −2 s −1 and k cat = 4.6 ± 0.8 M −2 s −1, and mechanistic interpretation of the catalytic rate law is given. The contribution of the catalytic path to the overall rate of decomposition changes from ca. 30% at pH = 8 to ca. 70% at pH = 6.